State of the Question and Future Challenges of Public Procurement in Peru Interview with Dr. Ricardo Salazar Chávez - Espino Layza, María Alejandra (2015)
The present interview has as purpose to give comprehensive overview about the currentsituation of public procurement in our country, with emphasis on the goals achieved and the possible challenges of the matter; all of this in the frame on the reform of public procurement law.